THE RATIONALE APPROACHES TO THE ASSESSMENT OF WORK PERFORMANCE OF THE STAFF OF THE ORGANIZATION - A. Mitrofanovа (Вестник университета)
The most important condition of increase of efficiency of activity of the organizations is the high performance staff. Therefore, the question of choosing a method of performance appraisal of employees is of great scientific and practical interest. It is this scientific problem addressed in this article. The author showed the main parameters of the performance appraisal of the staff. Submitted claims to the selection criteria for the performance appraisals of the staff. A comparative analysis of the main methods of performance appraisal of the staff, advantages and disadvantages of each method. The choice of the system of management by objectives as the most quality and effective method of performance appraisal of staff of the organization.